Preparation process and application of sulfur quantum dots with high fluorescence intensity and high stability

By using single-stranded DNA fragments as passivation agent and capping agent in the preparation process of sulfur quantum dots, combined with hydrogen peroxide etching and dialysis technology, the problems of low quantum yield and cumbersome preparation in the existing sulfur quantum dot preparation methods are solved, and high-efficiency synthesis of high fluorescence intensity and high stability sulfur quantum dots are achieved.

CN119662239AActive Publication Date: 2025-03-21UNIV OF JINAN
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411933297.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing sulfur quantum dot preparation methods have problems such as low quantum yield, cumbersome preparation, and long reaction time, which limits its wide application in the fields of detection, catalysis, imaging and treatment.

Method used

Single-stranded DNA fragments are used as passivation agent and capping agent, sulfur powder is added to the alkali liquid and stirred evenly, and the single-stranded DNA fragments are added, and the reaction is carried out under heating and stirring conditions, followed by hydrogen peroxide for etching, and finally high fluorescence intensity and high stability sulfur quantum dots are obtained through dialysis.

Benefits of technology

The fluorescence intensity and stability of sulfur quantum dots are significantly improved, the preparation process is simplified, the reaction time is shortened, the yield is improved, and efficient sulfur quantum dot synthesis is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662239A_ABST
    Figure CN119662239A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of sulfur quantum dots, and particularly discloses a preparation process and application of high-fluorescence-intensity and high-stability sulfur quantum dots. The process comprises the following steps: (1) adding powdered sulfur into alkali liquor, uniformly stirring, then adding a single-stranded DNA fragment, and then reacting under the conditions of continuous stirring, heating and heat preservation; and (2) adding hydrogen peroxide into the reaction liquid obtained in the step (1), and then continuously reacting under a continuous stirring condition. And dialyzing to obtain the sulfur quantum dot dispersion liquid. The process is simple, convenient and efficient, the fluorescence intensity, the stability and the biocompatibility of the sulfur quantum dots are remarkably improved, and a new thought and a new technical means are provided for synthesis of the sulfur quantum dots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sulfur quantum dot preparation, and in particular to a process for preparing sulfur quantum dots with high fluorescence intensity and high stability and applications thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Sulfur quantum dots (SQDs) are quasi-spherical fluorescent sulfur nanoparticles with nanometer-sized structures. They have excellent properties such as high fluorescence intensity, high photostability, resistance to photobleaching and low toxicity. These properties make sulfur quantum dots have broad application potential in a variety of fields such as detection, catalysis, imaging and therapy. There are many reports on the conversion of bulk elemental sulfur into nanosulfur, including physical methods such as grinding and etching and chemical methods such as oxidation. However, this is mainly limited to non-luminescent sulfur nanoparticles with a size greater than 10 nm, and there is still little research on sulfur quantum dots. The synthesis methods of sulfur quantum dots include: (1) acid etching oxidation method, which includes three main steps: physical contact process, phase interface reaction and in situ dissolution precipitation. (2) assembly-fission method, which requires a reaction time of up to 100 hours to achieve a dynamic equilibrium in which the fission-dominated assembly process is achieved, thereby obtaining monodisperse sulfur quantum dots. Traditional sulfur quantum dot preparation methods have problems such as low quantum yield, cumbersome preparation and long reaction time, which limit their further application. Summary of the invention

[0004] In view of this, the present invention provides a process for preparing sulfur quantum dots with high fluorescence intensity and high stability, which is not only simple and efficient, with high yield, but also significantly improves the fluorescence intensity and stability of sulfur quantum dots, and provides a new idea and technical means for the synthesis of sulfur quantum dots. Specifically, the technical solution of the present invention is as follows.

[0005] First, the present invention provides a process for preparing sulfur quantum dots with high fluorescence intensity and high stability, comprising the following steps: (1) Add sulfur powder to alkaline solution and stir evenly, then add single-stranded DNA fragments, and then react under continuous stirring and heating conditions.

[0006] (2) Add hydrogen peroxide to the reaction solution obtained in the above step (1), and then continue the reaction under continuous stirring. After completion, perform dialysis to obtain a sulfur quantum dot dispersion.

[0007] Furthermore, in step (1), the alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, etc. Preferably, the solvent of the alkali solution is any one of ultrapure water and deionized water.

[0008] Furthermore, in step (1), the mass fraction of the alkali solution is 8-15%. The sulfide formed by the alkali solution and the sulfur powder can further react with the sulfur powder to form unstable intermediate polysulfides (such as Na2S x ), which can further undergo fission reactions to release sulfur nanoparticles.

[0009] Furthermore, in step (1), the molar ratio of the sulfur powder, the solute in the alkali solution, and the single-stranded DNA fragment is 400-700: 1400-1600: 0.01-0.05. Optionally, the particle size of the sulfur powder is micrometer level.

[0010] Furthermore, in step (1), the single-stranded DNA fragment includes at least one of: PolyA 11 to PolyA 50, PolyC 11 to PolyC 50, PolyG 11 to PolyG 50, PolyT 11 to PolyT 50, etc. Preferably, the single-stranded DNA fragment is PolyA 11 to PolyA 50.

[0011] Furthermore, in step (1), the heating and heat preservation temperature is 60-90° C., and the reaction time is 12-24 hours. Optionally, the continuous stirring rate is 400-700 rpm.

[0012] Furthermore, in step (2), the initial mass fraction of hydrogen peroxide in the reaction solution is 4-10%. In this step, the present invention uses hydrogen peroxide to etch the surface of the sulfur nanoparticles, so that the larger sulfur nanoparticles are formed into smaller sulfur quantum dots, and the sulfur quantum dots have a stronger fluorescence intensity.

[0013] Furthermore, in step (2), the reaction is continued for 4 to 12 hours. Optionally, the continuous stirring rate is 400 to 700 rpm.

[0014] Furthermore, in step (2), the sulfur quantum dots are obtained by separating the base through dialysis membrane. Optionally, the sulfur quantum dots have a pH of 8-9.

[0015] Furthermore, in step (2), the sulfur quantum dots need to be stored in a low temperature environment of 2-8°C and protected from light.

[0016] Secondly, the present invention provides applications of the sulfur quantum dots obtained by the preparation process in the fields of detection, catalysis, imaging, medical treatment, etc.

[0017] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: the present invention uses single-stranded DNA fragments as passivators to prepare sulfur quantum dots. During the synthesis process, the amino groups (-NH2) on the surface of DNA are reacted with ammonium ions (NH4 + ) interacts with negatively charged groups on the surface of sulfur quantum dots (such as SO3 2- ) interact with each other, enhancing the dispersibility of SQDs. At the same time, the DNA fragment is covered on the surface of SQDs as a capping agent through electrostatic action, which can effectively prevent the aggregation of the formed SQDs and improve the stability of the SQDs, thereby obtaining sulfur quantum dots with high fluorescence intensity, high stability and good biocompatibility. In addition, compared with the traditional sulfur quantum dot preparation process, the preparation process proposed in the present invention greatly shortens the reaction time of the traditional assembly-fission method, which takes up to 100 hours, to less than 36 hours, significantly improving the production efficiency, indicating that the sulfur quantum dot preparation process proposed in the present invention is simpler and more efficient, and the yield of sulfur quantum dots is higher, providing new ideas and technical means for the synthesis of sulfur quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0019] Figure 1 This is a transmission electron microscopy image of the sulfur quantum dots prepared in the following Example 1.

[0020] Figure 2 The particle size distribution diagram of the sulfur quantum dots prepared in the following Example 1.

[0021] Figure 3 The fluorescence emission diagram of the sulfur quantum dots prepared in Example 1 below.

[0022] Figure 4 This is the fluorescence emission graph of the sulfur quantum dots prepared in the following Example 1 after standing for 15 days.

[0023] Figure 5 This is a transmission electron microscopy image of the sulfur quantum dots prepared in the following Example 2.

[0024] Figure 6 This is the fluorescence emission diagram of the sulfur quantum dots prepared in Example 2 below.

[0025] Figure 7 This is the fluorescence emission graph of the sulfur quantum dots prepared in the following Example 2 after standing for 15 days.

[0026] Figure 8 This is a transmission electron microscopy image of the sulfur quantum dots prepared in the following Example 3.

[0027] Fig. 9 This is the fluorescence emission diagram of the sulfur quantum dots prepared in Example 3 below.

[0028] Fig.10 This is the fluorescence emission graph of the sulfur quantum dots prepared in Example 4 below.

[0029] Fig.11 This is the fluorescence emission graph of the sulfur quantum dots prepared in Example 5 below.

[0030] Fig.12 This is the fluorescence emission graph of the sulfur quantum dots prepared in Example 6 below.

[0031] Fig.13 This is the fluorescence emission graph of the sulfur quantum dots prepared in Example 7 below.

[0032] Fig.14 This is the fluorescence emission graph of the sulfur quantum dots prepared in the following Example 7 after standing for 15 days.

[0033] Fig.15 This is the fluorescence emission graph of the sulfur quantum dots prepared in Example 8 below.

[0034] Fig.16 This is the fluorescence emission graph of the sulfur quantum dots prepared in the following Example 8 after standing for 15 days.

[0035] Fig.17 This is the fluorescence emission graph of the sulfur nanoparticles prepared in Example 9 below. DETAILED DESCRIPTION

[0036] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.

[0037] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.

[0038] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.

[0039] Example 1 A process for preparing sulfur quantum dots with high fluorescence intensity and high stability comprises the following steps: (1) Sodium hydroxide powder is added to ultrapure water to form a sodium hydroxide solution with a mass fraction of 11.7%, and then micron-sized sulfur powder is added. After stirring evenly, a single-stranded DNA fragment PolyA 30 (i.e., 30 adenines: AAAAA AAAAAAAAAA AAAAA AAAAA AAA) is added. The molar ratio of the sulfur powder, sodium hydroxide powder, and single-stranded DNA fragment is 625:1430:0.02. The obtained system is then heated to 70°C and stirred continuously at a rate of 450 rpm for 12 hours.

[0040] (2) Add hydrogen peroxide to the reaction solution obtained in the above step (1), wherein the initial mass fraction of hydrogen peroxide is 9%. Then stir the reaction continuously for 8 hours at a stirring rate of 450 rpm. Then dialyze the reaction solution with a 500 Da dialysis membrane to obtain sulfur quantum dots with a pH of 8.7. After completion, store the obtained sulfur quantum dot dispersion at 4°C.

[0041] The transmission electron microscopy image of the sulfur quantum dots prepared in this example is as follows Figure 1 As shown, it can be seen that the sulfur quantum dots are evenly distributed without agglomeration.

[0042] The particle size distribution of the sulfur quantum dots prepared in this example is shown in Figure 2 As shown, it can be seen that the average particle size of the sulfur quantum dots is 1.9 nm.

[0043] The fluorescence emission of the sulfur quantum dots prepared in this example and the fluorescence emission spectra after standing for 15 days are shown as follows: Figure 3 , Figure 4 As shown, it can be seen that the fluorescence emission wavelength of the quantum dots is around 420 nm, indicating that the sulfur quantum dots are successfully synthesized in this embodiment, and the fluorescence intensity of the quantum dots remains basically unchanged after standing for 15 days, proving that the quantum dots have high stability.

[0044] Example 2 A process for preparing sulfur quantum dots with high fluorescence intensity and high stability comprises the following steps: (1) Sodium hydroxide powder is added to ultrapure water to form a sodium hydroxide solution with a mass fraction of 10%, and then micron-sized sulfur powder is added. After stirring evenly, a single-stranded DNA fragment PolyA 11 (i.e., 11 adenines: AAAAA AAAAAA) is added. The molar ratio of the sulfur powder, sodium hydroxide powder, and single-stranded DNA fragment is 625:1430:0.02. The resulting system is then heated to 60°C and stirred at a rate of 700 rpm for 24 hours.

[0045] (2) Add hydrogen peroxide to the reaction solution obtained in the above step (1), wherein the initial mass fraction of hydrogen peroxide is 9%. Then stir continuously for 4 hours at a stirring rate of 700 rpm. Then dialyze the reaction solution with a 500 Da dialysis membrane to obtain sulfur quantum dots with a pH of 9. After completion, store the obtained sulfur quantum dot dispersion at 4°C.

[0046] The transmission electron microscopy image of the sulfur quantum dots prepared in this example is as follows Figure 5 As shown, it can be seen that the sulfur quantum dots are evenly distributed without agglomeration, and the average particle size of the sulfur quantum dots is 2.5 nm.

[0047] The fluorescence emission spectrum of the sulfur quantum dots prepared in this example is as follows Figure 6 As shown, it can be seen that the fluorescence emission wavelength of the quantum dots is around 410 nm, indicating that the sulfur quantum dots were successfully synthesized in this embodiment. Figure 7 This is the fluorescence spectrum of the quantum dots after standing for 15 days. The intensity remains basically unchanged, proving that the quantum dots have high stability.

[0048] Example 3 A process for preparing sulfur quantum dots with high fluorescence intensity and high stability comprises the following steps: (1) Sodium hydroxide powder is added to ultrapure water to form a sodium hydroxide solution with a mass fraction of 8%, and then micron-sized sulfur powder is added. After stirring evenly, a single-stranded DNA fragment PolyA 50 (i.e., 50 adenines in length: AAAAA AAAAAAAAAA AAAAA AAAAA AAAAA AAAAA AAAAA AAAAA AAAAA) is added. The molar ratio of the sulfur powder, sodium hydroxide powder, and single-stranded DNA fragment is 500:1500:0.03. The obtained system is then heated to 70°C and continuously stirred at a rate of 400 rpm for 12 hours.

[0049] (2) Add hydrogen peroxide to the reaction solution obtained in the above step (1), wherein the initial mass fraction of hydrogen peroxide is 5%. Then stir continuously for 7 hours at a stirring rate of 400 rpm. Then dialyze the reaction solution with a 500 Da dialysis membrane to obtain sulfur quantum dots with a pH of 8. After completion, the obtained sulfur quantum dot dispersion is stored at 8°C.

[0050] The transmission electron microscopy image of the sulfur quantum dots prepared in this example is as follows Figure 8 As shown, it can be seen that the sulfur quantum dots are evenly distributed without agglomeration, and the average particle size of the sulfur quantum dots is 2.8 nm.

[0051] The fluorescence emission spectrum of the sulfur quantum dots prepared in this example is as follows Fig. 9As shown, it can be seen that the fluorescence emission wavelength of the quantum dots is around 410 nm, indicating that the sulfur quantum dots were successfully synthesized in this embodiment.

[0052] Example 4 A process for preparing sulfur quantum dots with high fluorescence intensity and high stability comprises the following steps: (1) Sodium hydroxide powder is added to ultrapure water to form a sodium hydroxide solution with a mass fraction of 15%, and then micron-sized sulfur powder is added. After stirring evenly, a single-stranded DNA fragment PolyC 30 (i.e., 30 cytosines: CCCCC CCCCCCCCCC CCCCC CCCCC) is added. The molar ratio of the sulfur powder, sodium hydroxide powder, and single-stranded DNA fragment is 700:1600:0.05. The obtained system is then heated to 80°C and continuously stirred at a rate of 500 rpm for 20 hours.

[0053] (2) Add hydrogen peroxide to the reaction solution obtained in the above step (1), wherein the initial mass fraction of hydrogen peroxide is 4%. Then stir continuously for 6 hours at a stirring rate of 500 rpm. Then dialyze the reaction solution with a 500 Da dialysis membrane to obtain sulfur quantum dots with a pH of 8.3. After completion, store the obtained sulfur quantum dot dispersion at 2°C.

[0054] The fluorescence emission spectrum of the sulfur quantum dots prepared in this example is as follows Fig.10 As shown, it can be seen that the fluorescence emission wavelength of the quantum dots is between 410 and 450 nm, indicating that the sulfur quantum dots were successfully synthesized in this embodiment.

[0055] Example 5 A process for preparing sulfur quantum dots with high fluorescence intensity and high stability comprises the following steps: (1) Sodium carbonate powder is added to ultrapure water to form a sodium carbonate solution with a mass fraction of 12%, and then micron-sized sulfur powder is added. After stirring evenly, a single-stranded DNA fragment PolyG 30 (i.e., 30 guanines: GGGGG GGGGGGGGGGGGGGGGGGGGGGGGGG) is added. The molar ratio of the sulfur powder, sodium carbonate powder, and single-stranded DNA fragment is 400:1400:0.01. The obtained system is then heated to 70°C and continuously stirred at a rate of 450 rpm for 12 hours.

[0056] (2) Add hydrogen peroxide to the reaction solution obtained in the above step (1), wherein the initial mass fraction of hydrogen peroxide is 6.5%. Then stir continuously for 8 hours at a stirring rate of 450 rpm. Then dialyze the reaction solution with a 500 Da dialysis membrane to obtain sulfur quantum dots with a pH of 9. After completion, store the obtained sulfur quantum dot dispersion at 5°C.

[0057] The fluorescence emission spectrum of the sulfur quantum dots prepared in this example is as follows Fig.11 As shown, it can be seen that the fluorescence emission wavelength of the quantum dots is between 410 and 450 nm, indicating that the sulfur quantum dots were successfully synthesized in this embodiment.

[0058] Example 6 A process for preparing sulfur quantum dots with high fluorescence intensity and high stability comprises the following steps: (1) Potassium hydroxide powder is added to deionized water to form a potassium hydroxide solution with a mass fraction of 10%, and then micron-sized sulfur powder is added. After stirring evenly, a single-stranded DNA fragment PolyT 30 (i.e., 30 thymines in length: TTTTTTTTTT TTTTT TTTTT TTTTT TTTTT) is added. The molar ratio of the sulfur powder, potassium hydroxide powder, and single-stranded DNA fragment is 600:1550:0.04. The obtained system is then heated to 70°C and continuously stirred at a rate of 450 rpm for 12 hours.

[0059] (2) Add hydrogen peroxide to the reaction solution obtained in the above step (1), wherein the initial mass fraction of hydrogen peroxide is 10%. Then stir continuously for 12 hours at a stirring rate of 600 rpm. Then dialyze the reaction solution with a 500 Da dialysis membrane to obtain sulfur quantum dots with a pH of 8.5. After completion, store the obtained sulfur quantum dot dispersion at 4°C.

[0060] The fluorescence emission spectrum of the sulfur quantum dots prepared in this example is as follows Fig.12 As shown, it can be seen that the fluorescence emission wavelength of the quantum dots is between 410 and 450 nm, indicating that the sulfur quantum dots were successfully synthesized in this embodiment.

[0061] Example 7 A sulfur quantum dot preparation process comprises the following steps: (1) Sodium hydroxide powder was added to ultrapure water to form a sodium hydroxide solution with a mass fraction of 11.7%, and then micron-sized sulfur powder was added. After stirring evenly, a single-stranded DNA fragment (GAAGT GAAAA TGACA GAACA CAACA AAAATCGGGC) was added. The molar ratio of the sulfur powder, sodium hydroxide powder, and single-stranded DNA fragment was 625:1430:0.02. The obtained system was then heated to 70°C and stirred continuously at a rate of 450 rpm for 12 hours.

[0062] (2) Add hydrogen peroxide to the reaction solution obtained in the above step (1), wherein the initial mass fraction of hydrogen peroxide is 9%. Then stir the reaction continuously for 8 hours at a stirring rate of 450 rpm. Then dialyze the reaction solution with a 500 Da dialysis membrane to obtain sulfur quantum dots with a pH of 8.7. After completion, store the obtained sulfur quantum dot dispersion at 4°C.

[0063] The fluorescence emission spectrum of the sulfur quantum dots prepared in this example is as follows Fig.13 As shown in Figure 2, it can be seen that the fluorescence emission wavelength of the quantum dot is around 410nm. Fig.13 It can be seen that the fluorescence intensity of the sulfur quantum dots prepared in this example is about 5500, while the corresponding fluorescence intensity of Example 1 is about 8000. Fig.14 The fluorescence intensity of the sulfur quantum dots prepared in this example after standing for 15 days shows that the fluorescence intensity of the sulfur quantum dots at this time is 3500, which is about 2000 lower than the fluorescence intensity when just synthesized, proving that the stability of the quantum dots is poor. This means that the quantum dots synthesized by the mixed sequence DNA in this example are significantly lower in fluorescence intensity and stability than the quantum dots synthesized by the single base A in Example 1.

[0064] Example 8 A sulfur quantum dot preparation process comprises the following steps: (1) Sodium hydroxide powder was added to ultrapure water to form a sodium hydroxide solution with a mass fraction of 10%, and then micron-sized sulfur powder was added. After stirring evenly, double-stranded DNA (dsDNA: synthesized by annealing two single strands of AAAAA AAAAA A and TTTTT TTTTT T at 95°C for 2 minutes) was added. The molar ratio of the sulfur powder, sodium hydroxide powder, and double-stranded DNA fragment was 625:1430:0.02. The obtained system was then heated to 60°C and stirred continuously at a rate of 700 rpm for 24 hours.

[0065] (2) Add hydrogen peroxide to the reaction solution obtained in the above step (1), wherein the initial mass fraction of hydrogen peroxide is 9%. Then stir continuously for 4 hours at a stirring rate of 700 rpm. Then dialyze the reaction solution with a 500 Da dialysis membrane to obtain sulfur quantum dots with a pH of 9. After completion, store the obtained sulfur quantum dot dispersion at 4°C.

[0066] The fluorescence emission graph of the sulfur quantum dots prepared in this example is as follows Fig.15 As shown in Figure 2, it can be seen that the fluorescence emission wavelength of the quantum dot is around 410nm. Fig.15 It can be seen that the fluorescence intensity of the sulfur quantum dots prepared in this example is about 4000, while the corresponding fluorescence intensity of Example 2 is about 9500. Fig.16 The fluorescence intensity of the sulfur quantum dots prepared in this example after standing for 15 days shows that the fluorescence intensity of the sulfur quantum dots at this time is 3500, which is about 500 lower than the fluorescence intensity when just synthesized, proving that the stability of the quantum dots is average. This means that the quantum dots synthesized from double-stranded DNA in this example are significantly lower in fluorescence intensity and stability than the quantum dots synthesized from single-stranded DNA fragments in Example 2.

[0067] Example 9 A sulfur quantum dot preparation process comprises the following steps: (1) Sodium hydroxide powder is added to ultrapure water to form a sodium hydroxide solution with a mass fraction of 10%, and then micron-sized sulfur powder is added. After stirring evenly, a single-stranded DNA fragment PolyA 11 (i.e., 11 adenines: AAAAA AAAAAA) is added. The molar ratio of the sulfur powder, sodium hydroxide powder, and single-stranded DNA fragment is 625:1430:0.02. The resulting system is then heated to 60°C and stirred at a rate of 700 rpm for 24 hours.

[0068] (2) The reaction solution obtained in the above step (1) was dialyzed using a 500Da dialysis membrane. After dialyzation, the obtained sulfur particle product was stored at 4°C.

[0069] The fluorescence emission of the sulfur particle product prepared in this example is as follows Fig.17 As shown, it can be seen that without adding hydrogen peroxide, the sulfur particle product synthesized by this method has no fluorescence. This is because the sulfur particle product is not a sulfur quantum dot.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A process for preparing sulfur quantum dots with high fluorescence intensity and high stability, characterized in that: The steps include: (1) Add sulfur powder to alkaline solution and stir evenly, then add single-stranded DNA fragments, and then react under continuous stirring and heating conditions; (2) Adding hydrogen peroxide to the reaction solution obtained in the above step (1), and then continuing the reaction under continuous stirring conditions; after completion, dialyzing is performed to obtain a sulfur quantum dot dispersion.

2. The process for preparing sulfur quantum dots with high fluorescence intensity and high stability according to claim 1, characterized in that: In step (1), the alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution and sodium carbonate solution; preferably, the solvent of the alkali solution is any one of ultrapure water and deionized water.

3. The process for preparing sulfur quantum dots with high fluorescence intensity and high stability according to claim 1, characterized in that: In step (1), the mass fraction of the alkali solution is 8-15%.

4. The process for preparing sulfur quantum dots with high fluorescence intensity and high stability according to claim 1, characterized in that: In step (1), the molar ratio of the sulfur powder, the solute in the alkali solution, and the single-stranded DNA fragment is 400-700: 1400-1600: 0.01-0.05; optionally, in step (1), the particle size of the sulfur powder is micrometer level.

5. The process for preparing sulfur quantum dots with high fluorescence intensity and high stability according to claim 1, characterized in that: In step (1), the single-stranded DNA fragment includes at least one of PolyA 11 to PolyA 50, PolyC 11 to PolyC 50, PolyG 11 to PolyG 50, and PolyT 11 to PolyT 50. Preferably, the single-stranded DNA fragment is PolyA 11 to PolyA50.

6. The process for preparing sulfur quantum dots with high fluorescence intensity and high stability according to claim 1, characterized in that: In step (1), the heating and insulation temperature is 60-90° C., and the reaction time is 12-24 hours; optionally, in step (1), the continuous stirring rate is 400-700 rpm.

7. The process for preparing sulfur quantum dots with high fluorescence intensity and high stability according to claim 1, characterized in that: In step (2), the initial mass fraction of hydrogen peroxide in the reaction solution is 4-10%.

8. The process for preparing sulfur quantum dots with high fluorescence intensity and high stability according to claim 1, characterized in that: In step (2), the reaction is continued for 4 to 12 hours; optionally, in step (2), the continuous stirring rate is 400 to 700 rpm.

9. The process for preparing sulfur quantum dots with high fluorescence intensity and high stability according to any one of claims 1 to 8, characterized in that: In step (2), the sulfur quantum dots are separated by dialysis using a dialysis membrane; Optionally, in step (2), the pH of the sulfur quantum dots is 8-9; Optionally, in step (2), the sulfur quantum dots need to be stored in an environment of 2-8° C. and protected from light.

10. Application of the sulfur quantum dots obtained by the preparation process according to any one of claims 1 to 9 in the fields of detection, catalysis, imaging or medicine.

Citation Information

Patent Citations

  • Production of high-quantum-yield sulfur quantum dots and method for determining ascorbic acid thereof

    CN112067587A

  • Method for preparing quantum dots by taking sublimed sulfur as sulfur source

    CN112300794A

  • Application of sulfur quantum dot as fluorescent probe in tetracycline detection

    CN113390846A

  • Preparation method of water-soluble fluorescent sulfur quantum dots and application of water-soluble fluorescent sulfur quantum dots to detection of quercetin

    CN115746832A

  • Fluorescent sulfur quantum dot as well as synthesis method and application thereof

    CN115960603A